Effect of Traditional Chinese Medicine fumigation and washing combined with fine nursing on postoperative pain of patients with hemorrhoids (中药熏洗联合精细化护理对痔疮患者术后疼痛的影响) - CHEN Zhengrong (陈正荣) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) fumigation and washing combined with fine nursing on postoperative pain of patients with hemorrhoids. Methods Totally 40 patients undergoing surgical treatment for hemorrhoids were assigned to the control group and observation group according to the hospital admission sequence. Patients in the control group received routine nursing management, while those in the observation group were given TCM fumigation and washing combined with fine nursing. The Visual Analogue Scale (VAS) was used to measure the degree of pain at 24 h and 48 h after operation. The condition of anal edema and distention of the rectum were observed. Results The VAS scores at 24 h and 48 h after operation in the observation group were lower than those in the control group(P＜0. 01). At 72 h after surgery, the incidence rates of anal edema and distention of the rectum in the observation group were lower than those in the control group, with no significant difference(P＞ 0. 05). Conclusion The TCM fumigation and washing combined with fine nursing is effective to relieve the postoperative pain and reduce the degree of anal edema and distention of the rectum. (目的 探讨中药熏洗联合精细化护理对痔疮术后患者疼痛的影响。方法 选取40例痔疮手术患者, 按照入院时间先后顺序将其分成对照组和观察组, 各20例。对照组实施常规护理, 观察组实施中药熏洗联合精细化护理。对比两组术后24h、48 h伤口疼痛视觉模拟评分(VAS), 观察两组术后72 h肛缘水肿及肛门坠胀发生情况。结果 观察组术后24 h、48 h疼痛VAS评分低于对照组, 差异有统计学意义(P＜0. 01)。术后72 h观察组肛缘创面水肿及肛门坠胀症状发生率低于对照组, 但差异无统计学意义(P＞0. 05)。结论 痔疮患者术后使用中药熏洗联合精细化护理, 可减轻肛门局部疼痛, 降低肛缘创面水肿及肛门坠胀不适等情况发生。)